Comparative assessment of hydropower risks for fishes using the novel European fish hazard Index. (June 2022) - van Treeck, Ruben; Radinger, Johannes; Smialek, Nicole; Pander, Joachim; Geist, Juergen; Mueller, Melanie; Wolter, Christian
Highlights: The European Fish Hazard Index was tested at seven small hydropower plants. The EFHI reflected risks identified through impact assessments at these sites. Impact assessments can systematically underestimates hazards for fish. The EFHI can be improved by implementing additional modules. Abstract: In context of transitioning towards renewable energy, hydroelectricity has gained global relevance. However, hydropower plants have severe impacts on aquatic habitat and biota: Dams disrupt migration routes of diadromous and potamodromous fish species, degrade the hydro-morphology of streams and turbines cause high mortalities in fishes. To support risk assessment and mitigation, the European Fish Hazard Index EFHI identifies potentially harmful constellations of existing and planned hydropower plants adjusted to the reference fish assemblages of the affected stream sections. In this study, we applied the EFHI to seven small, low-head hydropower plants of various types and compared our results to those of extensive empirical fish mortality estimates independently conducted at the same sites. We illustrate how hydropower hazards go beyond turbine mortality and that the EFHI widely reflects site-specific risks of flow manipulations, entrainment, and upstream and downstream fish passage. Based on the EFHI results we found that environmental impact assessments based on the present fish community tend to underestimate hazards, particularly when the fish assemblage is already degraded. We further examined the EFHI's performance and identified some potential for future implementations of new fish mortality models and novel, fish safer turbines.